Cardiopulmonary Complications Following COVID-19 Vaccinations: A Systematic Review - Bnar J. Hama Amin; Dana H. Mohammed Saeed; Hadi Mohammed Abdullah; Zana H. Mahmood; Karokh Fadhil Hamahussein; Hussein M. Hamasalih; Sabah Jalal Hasan; Sanaa O. Karim; Marwan N. Hassan; Fahmi H. Kakamad; Berun A. Abdalla; Fakher Abdullah; et al. (Barw Medical Journal, 2023)
AbstractIntroductionClinical trials of COVID-19 vaccines were insufficient to detect uncommon adverse outcomes that are crucial for risk-benefit analyses and informing clinical practice post-vaccination. As a result, detection of infrequent adverse events has become a global research priority. The current study aims to estimate the rate of cardiopulmonary complications associated with COVID-19 vaccination.MethodsTwo databases and one search engine were explored to identify English language-related studies published up to January 2023.ResultsThe literature search turned up a total of 3974 relevant studies. Of them, 37 articles matched the inclusion criteria. Overall, seven studies from the United States. The mean age of patients was 25 years and about 77% of them were male. The most common reported consequence was inflammatory heart disease (myo-peri-cariditis), followed by pulmonary embolism (17%), and myocardial infarction (5%). The majority of complications were reported following mRNA COVID-19 vaccinations, particularly following the administration of the second dose. Pfizer has a slightly higher risk of cardiac complications following vaccination (4.1 per 100000 persons) than Moderna (3.7 per 100,000 persons).ConclusionAlthough cardiopulmonary complications associated with COVID-19 vaccinations are uncommon, they can be life-threatening. Therefore, more large-scale observational studies and review articles of those studies are strongly recommended.